2014
DOI: 10.4028/www.scientific.net/amm.695.3
|View full text |Cite
|
Sign up to set email alerts
|

Brief Review: Electrochemical Performance of LSCF Composite Cathodes - Influence of Ceria-Electrolyte and Metals Element

Abstract: Solid oxide fuel cells (SOFC) are an efficient and clean power generation devices. Low-temperature SOFC (LTSOFC) has been developed since high-temperature SOFC (HTSOFC) are not feasible to be commercialized because high in cost. Lowering the operation temperature has caused substantial performance decline resulting from cathode polarization resistance and overpotential of cathode. The development of composite cathodes regarding mixed ionic-electronic conductor (MIEC) and ceria based materials for LTSOFC signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The increase of cathode polarization resistance substantially reduces the electrochemical performance [2]. Previously, research studies reported that the design of a high-performance electrode with a low polarization resistance such as composite cathode has the potential to solve the said problem [1,3]. could enhance the area of TPB and increase the performance of the SOFC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of cathode polarization resistance substantially reduces the electrochemical performance [2]. Previously, research studies reported that the design of a high-performance electrode with a low polarization resistance such as composite cathode has the potential to solve the said problem [1,3]. could enhance the area of TPB and increase the performance of the SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…This property is suitable for its good catalytic activity, high electrical conductivity, and relatively low cost. Furthermore, the use of this metal also improves cathode microstructure since the melting point of Ag is 961 °C, which will aid the sintering behavior at cathode [14][15]. This study focuses on the investigation of the LSCF-SDCC-Ag composite cathode to suit the low-temperature application (400-600 °C) of solid oxide fuel cell applications.…”
Section: Introductionmentioning
confidence: 99%